Пух, летающая собака - Одинцова Людмила (Лапы, крылья и хвосты, 2011)
Экземпляры: СФ-5 (20120830) / Инвентарный номер: 41042z5 / Цена: 183.38 / Сис.шифр: 84(2) / Авт.знак: О-42 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)